Personality in the wild zebra finch: exploration, sociality, and reproduction. (23rd February 2015) - McCowan, Luke S.C.; Mainwaring, Mark C.; Prior, Nora H.; Griffith, Simon C.
Lay Summary: Although research has shown that animals have distinct personalities, much of this work has been conducted on animals studied in captivity. We studied the personalities of wild zebra finches. We found that one aspect of their personality (exploratory behavior) when brought into captivity did not reflect their personality when finding food in the wild. Moreover, it was not related to their social or reproductive behavior as we expected based on work with captive populations. Abstract : Although personality has been well studied in a wide range of species, relatively few studies have assessed if behavior in standardized captive tests is predictive of behavior in the wild. We captured wild zebra finches around 2 breeding colonies and assayed their exploratory behavior with a novel environment test. The birds' foraging behavior in the wild was also measured with the use of a passive integrated transponder tag system to monitor their use of feeders that were periodically moved around the colonies to assess exploratory behavior and sociality. During the same period, individuals' reproductive success was monitored at the nest-boxes being used in this area. We found that our measures of sociality, wild, and captive exploration were repeatable, but contrary to our predictions, exploration in the novel environment test was not significantly correlated with exploration of feeders in the wild. We failed to find a predicted negative relationship between exploration and sociality, instead finding a significant positive correlation between exploration in the novel environment and sociality. Finally, we found little evidence that any of our measured personality traits influenced reproductive success at the colony, either individually or when the interactions between the personalities of both members of the pair were taken into account. The only exception was that highly exploratory males (assayed with wild feeder behavior) were more likely to make breeding attempts than less exploratory males. Our results suggest that researchers should use caution when using tests such as the classic novel environment test to make inferences about personality in wild populations.